TEKNIK SOSIODRAMA EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA DALAM MENINGKATKAN KOMUNIKASI INTERPERSONAL DI SEKOLAH MENENGAH ATAS PLUS BUSTANUL ULUM MLOKOREJO JEMBER - Masrukhin, Akhmad Rudi; Uke, Ora Gorez; Filanda Azizi, Zilvi; Aminullah, Aminullah (Journal of Education Counseling, 2022)
This research focuses on how the effectiveness of group counseling services using the sociodrama technique in improving interpersonal communication. In order for research to achieve optimal results, the purpose of this study is to find out the effectiveness of group guidance services using the sociodrama technique in improving interpersonal communication of class XI students at SMA Plus Bustanul Ulum Mlokorejo in the 2021/2022 academic year. This study used quantitative methods, with the type of experimental research and the One Group Pretest Posttest Design. The sampling technique in this study was a purposive sampling technique with a sample of 20 students. Data collection techniques include: Questionnaires, interviews, observation and documentation. The data analysis technique in this study was paired sample t-test using SPSS version 25. Group guidance is a guidance service provided in a group setting. To help improve students' interpersonal communication, it can be done through group guidance services with the sociodrama technique, because it was chosen. specifically in improving interpersonal communication because of the sociodrama technique students can interact with each other between group members with various experiences, knowledge, ideas or ideas that are expected to provide students with an understanding of interpersonal communication.Keywords: Group Guidance, Socidrama Techniques, Interpersonal Communicatio